Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

Hydrological Outlook UK: an operational streamflow and groundwater level forecasting system at monthly to seasonal time scales - Christel Prudhomme; Jamie Hannaford; Shaun Harrigan; David Boorman; Jeff Knight; Victoria Bell; Christopher Jackson; Cecilia Svensson; Simon Parry; Nuria Bachiller-Jareno; Helen Davies; Richard Davis; et al. (Hydrological Sciences Journal, 2017)

Emission of Volatile Compounds from Apple Plants Infested with Pandemis heparana Larvae, Antennal Response of Conspecific Adults, and Preliminary Field Trial - Valentino Giacomuzzi; Luca Cappellin; Iuliia Khomenko; Franco Biasioli; Stefan Schütz; Marco Tasin; Alan L. Knight; Sergio Angeli (Journal of Chemical Ecology, 2016)

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

Combining Mutualistic Yeast and Pathogenic Virus — A Novel Method for Codling Moth Control - Alan L. Knight; Peter Witzgall (Journal of Chemical Ecology, 2013)

Apple Volatiles Synergize the Response of Codling Moth to Pear Ester - Ashraf M. El-Sayed; Lyn Cole; John Revell; Lee-Anne Manning; Andrew Twidle; Alan L. Knight; Vincent G. M. Bus; David M. Suckling (Journal of Chemical Ecology, 2013)

“This is not an Apple”–Yeast Mutualism in Codling Moth - Peter Witzgall; Magali Proffit; Elzbieta Rozpedowska; Paul G. Becher; Stefanos Andreadis; Miryan Coracini; Tobias U. T. Lindblom; Lee J. Ream; Arne Hagman; Marie Bengtsson; Cletus P. Kurtzman; Jure Piskur; et al. (Journal of Chemical Ecology, 2012)

Global patterns in the biogeography of bacterial taxa - Diana R. Nemergut; Elizabeth K. Costello; Micah Hamady; Catherine Lozupone; Lin Jiang; Steven K. Schmidt; Noah Fierer; Alan R. Townsend; Cory C. Cleveland; Lee Stanish; Rob Knight (Environmental Microbiology, 2011)
Summary Bacteria control major nutrient cycles and directly influence plant, animal and human health. However, we know relatively little about the forces shaping their large‐scale ecological ranges. Here, we reveal patterns in the distribution of individual bacterial taxa at multiple levels of phylogenetic resolution within and between Earth's major habitat types. Our analyses suggest that while macro‐scale habitats structure bacterial distribution to some degree, abundant bacteria (i.e. detectable using 16S rRNA gene sequencing methods) are confined to single assemblages. Additionally, we show that the most cosmopolitan taxa are also the most abundant in individual assemblages. These results add to the growing body of data that support that the diversity of the overall bacterial metagenome is tremendous. The mechanisms governing microbial distribution remain poorly understood, but our analyses provide a framework with which to test the importance of macro‐ecological environmental gradients, relative abundance, neutral processes and the ecological strategies of individual taxa in structuring microbial communities.

Quality matters: resource quality for hosts and the timing of epidemics - Spencer R. Hall; Christine J. Knight; Claes R. Becker; Meghan A. Duffy; Alan J. Tessier; Carla E. Cáceres (Ecology Letters, 2009)
Epidemiologists increasingly realize that species interactions (e.g. selective predation) can determine when epidemics start and end. We hypothesize here that resource quality can also strongly influence disease dynamics: epidemics can be inhibited when resource quality for hosts is too poor and too good. In three lakes, resource quality for the zooplankton host ( Daphnia dentifera ) was poor when fungal epidemics ( Metschnikowia bicuspidata ) commenced and increased as epidemics waned. Experiments using variation in algal food showed that resource quality had conflicting effects on underlying epidemiology: high‐quality food induced large production of infective propagules (spores) and high birth rate but also reduced transmission. A model then illustrated how these underlying correlations can inhibit the start of epidemics (when spore production/birth rate are too low) but also catalyse their end (when transmission becomes too low). This resource quality mechanism is likely to interface with other ones controlling disease dynamics and warrants closer evaluation.

Will loss of snow cover during climatic warming expose New Zealand alpine plants to increased frost damage? - Peter Bannister; Tanja Maegli; Katharine J. M. Dickinson; Stephan R. P. Halloy; Allison Knight; Janice M. Lord; Alan F. Mark; Katrina L. Spencer (Oecologia, 2005)

A pear-derived kairomone with pheromonal potency that attracts male and female codling moth, Cydia pomonella (L.) - Douglas M. Light; Alan L. Knight; Clive A. Henrick; Dayananda Rajapaska; Bill Lingren; Joseph C. Dickens; Katherine M. Reynolds; Ronald G. Buttery; Gloria Merrill; James Roitman; Bruce C. Campbell (The Science of Nature, 2001)

Attractants from Bartlett pear for codling moth, Cydia pomonella (L.), larvae - Alan L. Knight; Douglas M. Light (The Science of Nature, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)